Neuropharmacological modulation of the aberrant bodily self through psychedelics. (January 2020) - Ho, Jasmine T.; Preller, Katrin H.; Lenggenhager, Bigna
Highlights: Many psychiatric disorders include alterations of the bodily self. Disorders may link to dysfunctional predicting coding of multisensory information. 5-HT2A receptor agonism could remediate atypical perceptions of the bodily self. Disintegration of associative and somatomotor networks could promote remediation. Psychedelics may mediate these processes via predictive coding desynchronization. Abstract: As a continual source of sensory input and fundamental component of self-referential processing, the body holds an integral modulatory role in cognition. In a healthy state, predictive coding of multisensory integration promotes the construction of a coherent self. However, several psychiatric disorders comprise aberrant perceptions of the bodily self that are purported to involve discrepancies in the integration and updating of multisensory systems. Changes in functional connectivity of somatomotor and high-level association networks in these disorders could be successfully remediated through 5-HT2A receptor agonism via psychedelics. Reported alterations of bodily self-awareness during psychedelic experiences allude to a potentially central role of the bodily self. In this article, we bridge the domains of (aberrant) bodily self-awareness and psychedelics by discussing the predictive coding mechanisms underlying the bodily self and psychedelics. Furthermore, we propose that psychedelically-induced desynchronization of predictive coding might involve modulation of somatomotor, sensorimotor, and high-level association networks that could remediate aberrant perceptions of the bodily self.